Trajectories of perioperative serum CEA and non-small cell lung cancer prognosis: a retrospective longitudinal cohort study - Ma, Yuyang; Pan, Xiaoyin; Cui, Jiameng; Lu, Wanzhu; Sun, Gege; Pan, Junlong; Dong, Xiao; Hu, Kejia; Li, Wenyuan; Tu, Huakang; Wu, Xifeng (Frontiers in Oncology, 2025)
BackgroundThe role of postoperative carcinoembryonic antigen (CEA) levels in non-small lung cancer (NSCLC) prognostic evaluation remains unclear. Additionally, the dynamic changes in CEA levels during the perioperative period have not been fully characterized.MethodsWe retrospectively reviewed stage I-IIIA NSCLC patients who underwent curative resection. A latent class growth mixed model was employed to categorize patients into distinct CEA trajectory groups. The Kaplan-Meier method assessed the relationship between CEA trajectory groups and recurrence-free survival (RFS) and overall survival (OS). Multivariate analysis of perioperative CEA levels in relation to RFS and overall survival OS was performed using Cox proportional hazards regression.ResultsA total of 5733 patients were included in our study. Elevated postoperative CEA levels were associated with higher risks of recurrence (HR = 2.64, 95% CI: 1.65-4.23) and mortality (HR = 3.34, 95% CI: 2.09-5.80) compared to normal CEA levels. Furthermore, patients with normal preoperative CEA but elevated postoperative levels also had higher risks of recurrence (HR = 3.00, 95% CI: 1.77–5.10) and mortality (HR = 3.30, 95% CI: 1.79–6.07). Three CEA trajectory categories were identified: low-stable, early-rising, and later-rising. Compared to the low-stable group, the early-rising group had significantly higher risks of recurrence (HR = 10.84, 95% CI: 5.57-21.10) and mortality (HR = 13.37, 95% CI: 5.45-32.81). The later-rising group had lower, but still significant, risks of recurrence (HR = 3.56, 95% CI: 1.62-7.81).ConclusionContinuous postoperative monitoring of CEA levels in NSCLC patients is essential, especially for those with elevated postoperative CEA levels.